Characterization of tumorspheres generated from nasopharyngeal carcinoma cell line, TW06 and chemoresistance to docetaxel and oxaliplatin - Goh, Iris Wen Li; Yip, Wai Kien; Seow, Heng Fong (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2015)
In this study, tumorspheres were generated from TW06 nasopharyngeal carcinoma cell line and examined their expression of putative cancer stem-like cell surface markers and drug sensitivity. The rate of tumorsphere expansion from dissociated late passage TW06 tumorspheres (≥ passage 15) was higher than that from parental cells and dissociated 10-day-old (passage 0) tumorspheres. The expression of CD24 surface marker was lost in the generation of tumorspheres and the loss was reversible after differentiating the tumorspheres in monolayer culture conditions. Drug sensitivity assay showed that late passage tumorspheres were resistant to docetaxel and oxaliplatin treatment. Our data suggest that serially passaged tumorspheres possess the characteristics of CSCs that render them a suitable preclinical in vitro model for evaluating anticancer drug efficacy and elucidating the underlying mechanisms of drug resistance.